P-002 Zinc restores testicular integrity and function in HAART-treated male Wistar rats via modulation of Nrf2/NFkB pathway and downregulation of caspase 3 signaling. (30th June 2022) - Hamed, M; Akhigbe, R
Abstract: Study question: Will zinc treatment attenuate highly active antiretroviral drugs (HAART)-induced testicular dysfunction when used concomitantly? Summary answer: Zinc blunted HAART-induced reproductive toxicity by attenuating testicular and epididymal oxido-inflammatory injury via modulation of Nrf2/NFkB signaling and downregulation of caspase 3-mediated apoptosis. What is known already: The use of HAART has been established to be effective in the management of HIV; however, it has also been reported to induce male reproductive dysfunction. Studies have revealed that HAART impairs fertility by reducing libido and inducing testicular and sperm damage via an oxidative stress-sensitive pathway. On the other hand, zinc has been shown to enhance reproductive function by improving testicular redox state. Till date, no study has reported the impact of zinc co-administration with HAART on testicular integrity and function, spermatogenesis and sperm quality, and sexual behaviour. Study design, size, duration: This is a prospective experimental study using animal model. Forty sexually mature inbred male Wistar rats of comparable age and weight were used for the study. The study lasted 8 weeks. Participants/materials, setting, methods: Animals were acclimatized for two weeks, then randomly assigned into four groups (n = 10). The control rats received 0.5mL of distilled water as vehicle, zinc-treated animals received zinc supplement, HAART-treated rats received a cock-tail of antiretroviral drugs (Efavirenz, Lamivudine, and Tenofovir), while the Zn + HAART-treated rats received treatment as zinc-treated as well as HAART-treated. The doses of drugs used were the Human Equivalent doses for rats. Main results and the role of chance: Zinc blunted HAART-induced rise in testicular activities of gamma glutamyl transferase, lactate dehydrogenase activity, concentrations of lactate, and reduced testicular sorbitol dehydrogenase activity. Also, zinc ameliorated HAART-induced decline in the activities of testicular and epididymal superoxide dismutase, catalase, glutathione peroxidase, and glutathione-S-transferase, as well as glutathione and Nrf2 concentrations, and rescued HAART-induced increase in testicular and epididymal concentrations of uric acid, malondialdehyde, 8-OHdG, xanthine oxidase and MPO activities, and TNF-α, IL-1β, and NF- k B levels. This was associated with dampening of HAART-led upregulation of caspase 3 activity by zinc. Furthermore, zinc alleviated HAART-led reduction in spermatogenesis and sperm quality, serum nitric oxide and penile cGMP, and circulatory levels of FSH, LH, and testosterone, as well as testicular concentrations of 3β-HSD, 17β-HSD, and testosterone. In addition, zinc prevented HAART-induced sexual dysfunction and poor fertility indices. Limitations, reasons for caution: This study was conducted in a rat model; hence findings should be extrapolated to human with care. Thus, clinical trials are recommended to validate these findings. Wider implications of the findings: For the first time, we demonstrated the protective role of zinc treatment on HAART-induced male reproductive dysfunction. These findings provide further mechanisms through which HAART induces male infertility, and the possible protective role of zinc. Trial registration number: not applicable